Temperature Equation of State of an Explosive Reactant - Partom, Yehuda (European Journal of Applied Sciences, 2022)
To use our TDRR reactive flow model [1-4], we need a temperature equation of state for both compressive and tensile deformation. Such an equation of state is usually constructed around a reference curve in the PV (pressure and specific volume) plane. We show how to construct these equations of state for V<V0, where the reference curve is the shock Hugoniot, and for VV0, where the reference curve is the axis P=0.